Respon Guru terhadap Platform Merdeka Mengajar dalam Digitalisasi Pendidikan di Kabupaten Gowa: Penelitian - Suarlin; Sukawati, Herlina; Hardiyanti Arhas, Sitti; MY, Nurfadila (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze teachers' responses to the convenience and ease of use of Merdeka Mengajar Platform and evaluate its impact on teaching skills and professional competence of teachers in Gowa Regency. This research also identifies the obstacles faced and the level of teacher satisfaction with the platform as part of the digital transformation of education. The method used is descriptive quantitative with survey techniques through a Likert scale questionnaire. The research was conducted in Gowa Regency involving teachers from various levels of education as respondents. Validity test was conducted through Pearson correlation analysis, while reliability was tested using Cronbach's Alpha. Data analysis was conducted using descriptive statistics. The results showed that teachers responded very positively to the convenience and ease of use of the PMM, with high ratings on the aspects of appearance, navigation, and feature relevance. PMM is proven to improve pedagogical skills, teaching confidence, and creativity in using ICT. However, significant barriers still arise in the form of limited internet networks, devices, and time. The implications of this study suggest the need for policy interventions related to improving digital infrastructure and ongoing technical assistance training to support the continued use of this platform in the national education ecosystem.